Analisis Hubungan Antara Implementasi Manajemen Strategik dan Intensitas Kewirausahaan Organisasi - Andhi Johan; Nirmala (Majalah Imiah Manajemen & Bisnis, 2020)
This study examines the relationship between corporate entrepreneurship intensity and strategic management practices in a sample of Small and Medium Entreprices (SMEs). The strategic management practices include: scanning intensity, planning flexibility, planning horizon, locus of planning, and control attributes (strategic controls and financial controls). The results of the study indicated a positive relationship between corporate entrepreneurship intensity and scanning intensity, planning flexibility, locus of planning, and strategic controls. Those relationships are in line with the proposed hipothesis. While the two hypotheses proposed, that there is a negative relationship between firm entrepreneurship intensity with planning horizon and financial controls, not empirically proven. The results of this research may be useful to firms that are trying to become more entrepreneurial and may help researchers better understand the subtleties of the interface between strategic management and corporate entrepreneurship intensity, especially in the nature of SMEs.